Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/rcm.2998
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependencies of high‐temperature reduction on conversion products and their isotopic signatures

Abstract: High-temperature reduction (HTR) is widely used for oxygen and hydrogen isotope determination. Decomposition of cellulose, sucrose and polyethylene foil by HTR is quantitative for temperatures around 1450 degrees C. For lower reaction temperature production of CO(2), water and the deposition of carbon inside the reactor are significant and thus the element of interest for isotopic analysis is split into different pools, leading to isotope fractionation. After reduction of cellulose or sucrose at 1125 degrees C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 17 publications
2
42
0
Order By: Relevance
“…Pyrolysis was performed in a ceramic tube of glassy carbon at 1,450°C under a continuous flow of He at 100 ml min À1 . The gas obtained was separated from residual gases by molecular sieving through a 5-Å column (length, 3 m) at 50°C (Werner et al 1996;Bo¨hlke et al 2003;Leuenberger and Filot 2007 Table 1). The maximum air temperature was negatively correlated with rice yield (Fig.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…Pyrolysis was performed in a ceramic tube of glassy carbon at 1,450°C under a continuous flow of He at 100 ml min À1 . The gas obtained was separated from residual gases by molecular sieving through a 5-Å column (length, 3 m) at 50°C (Werner et al 1996;Bo¨hlke et al 2003;Leuenberger and Filot 2007 Table 1). The maximum air temperature was negatively correlated with rice yield (Fig.…”
Section: Stable Isotope Analysismentioning
confidence: 99%
“…About one‐sixth of the carbon in the cellulose nitrate molecule is deposited as elemental carbon within the reactor 15. The amount of the trace gases CO 2 and H 2 O depends on the reaction temperature and on the gas flow conditions in the reactor 16. While temperature can be considered as constant for different measurement runs, changes in the gas flow conditions may occur due to variations in the reactor packing after cleaning and refilling the reactor.…”
Section: Resultsmentioning
confidence: 99%
“…This is either due to low operating temperatures15 or to a fixed technical setup which allows the injection of only one sample type during a single run (either liquid or solid). Furthermore, the utilization of high‐temperature pyrolysis for oxygen and carbon isotope analysis showed that reasonable results are only obtained if a proper calibration is applied 15, 16. Such a calibration requires appropriate reference materials whose δ 2 H values can most reliably be normalized to the V‐SMOW/SLAP scale if direct alternating measurement of reference waters and organic materials is possible.…”
mentioning
confidence: 99%
“…After being encapsulated in silver, 0.2 mg (±10%) of α‐cellulose was pyrolized over glassy carbon at 1450°C and simultaneous measurements of oxygen and carbon isotope ratios (δ 13 C and δ 18 O) were performed (Leuenberger and Filot, ; Loader and Waterhouse, ) using a ThermoQuest TCEA interfaced with a Thermo Delta V Advantage IRMS. The isotopic ratios are reported in per mil (‰) relative to the Vienna Standard Mean Ocean Water (VSMOW) for oxygen, and Vienna Pee Dee Belemnite (VPDB) for carbon (Coplen, ), respectively, using the traditional δ (delta) notation.…”
Section: Methodsmentioning
confidence: 97%